From Having Sympathy to Showing Empathy for the Demented: A Narratological Study of the Perspectives of Characters with Dementia in Away from Her, Still Alice, and The Father (American & British Studies Annual, 2024)
The present study discusses the challenge of choosing an appropriate narrative structure for representing the unreliable perspective of characters with dementia in cinematic adaptations. The argument is that the chosen frameworks and techniques should create sympathy and empathy in readers/audience, and the ideal empathetic adaptation should choose narratological frameworks with the lowest level of coherence, narrative distancing and external focalization. As prototypical examples, the study focuses on the cinematic adaptations of three literary texts which treat dementia as their main thematic concern: Away from Her (2007), Still Alice (2014), and The Father (2021). The study employs critical categories and conceptualizations proposed by Per Krogh Hansen regarding unreliable perspectives, as well as the critical views of Gulce Torun, the latter of whom domesticates Endel Tulving’s mnemonic functions of episodic memory in her narratological discussions regarding the rapport between unreliable perspectives and memory. The analysis identifies features of intranarrational, internarrational, and extratextual unreliability as well as corresponding features of semantic, episodic, archival, and constructivist memory in the adaptations.
Keywords: dementia; unreliability; Per Krogh Hansen; memory; narrational perspective